Otolith microchemistry: Insights into bioavailable pollutants in a man-made, urban inlet - Andronis, C.; Evans, Noreen; McDonald, B.; Nice, H.; Gagnon, Marthe Monique (Elsevier, 2017)
Black bream (Acanthopagrus butcheri) were collected from an artificial inlet, Claisebrook Cove, Western Australia. Claisebrook Cove is adjacent to an historic contaminated site that was remediated during the 1990s. It was later identified as a priority area due to elevated levels of sediment contaminants including Zn, Cu, and Pb. Black bream were collected from this cove in 2005 and 2012 and their otoliths were analysed by laser ablation inductively coupled plasma mass spectrometry of the most recent growth zone. Levels of Zn and Mn, which are metabolically regulated, did not correlate with sediment contamination. However, reduction in sediment Cu levels over time coincided with reduced Cu otolith levels from 2005 to 2012. Results indicate that the elemental composition of the marginal edge of Black bream otoliths can identify bioavailable contaminants in an urban estuary and, with monitoring, can be utilized to establish long-term trends.